2015
DOI: 10.3109/10428194.2015.1106533
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism pathways in chronic lymphocytic leukemia

Abstract: Alterations in CLL cell metabolism have been studied by several investigators. Unlike normal B lymphocytes or other leukemia cells, CLL cells, like adipocytes, store lipids and utilize free fatty acids (FFA) to produce chemical energy. None of the recently identified mutations in CLL directly affects metabolic pathways, suggesting that genetic alterations do not directly contribute to CLL cells’ metabolic reprogramming. Conversely, recent data suggest that activation of STAT3 or downregulation of microRNA-125 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 98 publications
(99 reference statements)
3
54
0
Order By: Relevance
“…A higher oxidant capacity was associated with higher WBC and lymphocyte counts, as well as with elevated β 2 ‐microglobulin levels. The correlation with WBC and lymphocyte count can be explained by considering that most of oxidants detected in the blood serum derive presumably from these cells, as above reported . A direct link between the oxidant capacity and β 2 ‐microglobulin is more difficult to postulate based on the lack of data on this issue, but this correlation is most likely due to the association of β 2 ‐microglobulin levels with the tumour burden.…”
Section: Discussionmentioning
confidence: 78%
“…A higher oxidant capacity was associated with higher WBC and lymphocyte counts, as well as with elevated β 2 ‐microglobulin levels. The correlation with WBC and lymphocyte count can be explained by considering that most of oxidants detected in the blood serum derive presumably from these cells, as above reported . A direct link between the oxidant capacity and β 2 ‐microglobulin is more difficult to postulate based on the lack of data on this issue, but this correlation is most likely due to the association of β 2 ‐microglobulin levels with the tumour burden.…”
Section: Discussionmentioning
confidence: 78%
“…Many forms of leukaemia are CD5 + , and early-generated B1-like B cells have been demonstrated to be a source of chronic lymphocytic leukaemia (CLL) (Hayakawa et al, 2016). CLL has been found to have many metabolic features in common with our observations in B1 B cells, including high rates of lipid storage, glycolysis, and oxidative phosphorylation (Jitschin et al, 2014;Doughty, 2006;Tili et al, 2012;Rozovski et al, 2016). Understanding whether the physiological metabolic phenotype we have described in B1 B cells contributes to their malignant potential remains an area for further study, as does the potential for inhibition of fatty acid synthesis or autophagy as a novel therapeutic target.…”
Section: Autophagy Maintains B1 B Cell Metabolic Homeostasismentioning
confidence: 71%
“…Unlike normal B lymphocytes, CLL cells, like adipocytes, store lipids and utilize free fatty acids (FFA) to produce chemical energy. Apparently, none of the known gene mutations occurring in CLL directly affects metabolic pathways, while activation of STAT3 or downregulation of microRNA-125 levels seems to plays a crucial role [16]. Conversely, only very few data concerning lipid metabolism in human lymphomas have been so far published.…”
mentioning
confidence: 99%
“…In the study, it was shown how etomoxir and ranolazine, two fatty acid oxidation inhibitors, and orlistat, a well-known anti-obesity drug which works as an inhibitor of lipolysis, inhibited the proliferation of neoplastic cells, while sensitizing them to apoptosis induction [15]. In chronic lymphocytic leukemia (CLL) metabolism alterations have been studied by several Authors [16]. Unlike normal B lymphocytes, CLL cells, like adipocytes, store lipids and utilize free fatty acids (FFA) to produce chemical energy.…”
mentioning
confidence: 99%